2013
DOI: 10.1371/journal.pone.0083850
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Underlying Burden of Pertussis in Adolescents and Adults in Southern Ontario, Canada

Abstract: Despite highly successful vaccination programs and high vaccine uptake, both endemic pertussis and periodic pertussis outbreaks continue to occur. The under-recognized role of adolescents and adults in disease transmission, due to waning immunity following natural infection and vaccination, and reduced likelihood of correct diagnosis, may contribute to pertussis persistence. We constructed a mathematical model to describe the transmission of pertussis in Southern Ontario in both pre-vaccine and vaccine eras, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 41 publications
1
14
0
2
Order By: Relevance
“…Based on R 0 estimates, pertussis is considered far more contagious than polio, smallpox, rubella, mumps, and diphtheria (262,263). Studies showed that one infected person can transmit B. pertussis to as many as 12 to 17 other susceptible individuals, while R 0 values for polio and smallpox (5 to 7), rubella (6 to 7), mumps (4 to 7), and diphtheria (6 to 7) are substantially lower (261)(262)(263)(264)(265)(266). Kretzschmar et al found that the R 0 for pertussis across five European countries (Finland, Germany, Italy, The Netherlands, and the United Kingdom) during the 1990s was approximately 5.5, which is lower than R 0 estimates in previous studies (267).…”
Section: Transmission Dynamics Of Pertussismentioning
confidence: 99%
See 1 more Smart Citation
“…Based on R 0 estimates, pertussis is considered far more contagious than polio, smallpox, rubella, mumps, and diphtheria (262,263). Studies showed that one infected person can transmit B. pertussis to as many as 12 to 17 other susceptible individuals, while R 0 values for polio and smallpox (5 to 7), rubella (6 to 7), mumps (4 to 7), and diphtheria (6 to 7) are substantially lower (261)(262)(263)(264)(265)(266). Kretzschmar et al found that the R 0 for pertussis across five European countries (Finland, Germany, Italy, The Netherlands, and the United Kingdom) during the 1990s was approximately 5.5, which is lower than R 0 estimates in previous studies (267).…”
Section: Transmission Dynamics Of Pertussismentioning
confidence: 99%
“…Pertussis outbreaks have been also reported in North America, Europe, and Australia (182,195,202,203,254,264,(435)(436)(437)(438). In contrast, few data are available from Latin American, Asian, and African countries compared with Europe and the United States (174,(439)(440)(441)(442)(443)(444)(445)(446).…”
Section: Control Measures For Pertussis Outbreaksmentioning
confidence: 99%
“…It is also possible that sociodemographic features such as income may affect reported rates of pertussis. It is likely that pertussis among both adolescents and adults in the US is endemic but largely underreported [9,10]. Higher income may influence who is more likely to seek care or to receive testing for nonspecific respiratory diseases, including many cases of pertussis.…”
Section: Introductionmentioning
confidence: 99%
“…7 Pertussis among adolescents and adults may present with atypical or milder symptoms, 8 , 9 leading to under-diagnosis and under-reporting, and the risk of transmission to more vulnerable groups which could contribute to outbreaks in the population. 10 …”
Section: Introductionmentioning
confidence: 99%